Imaging in gynecological disease (8): ultrasound characteristics of recurrent borderline ovarian tumors. (25th March 2013) - Franchi, D.; Boveri, S.; Fruscio, R.; Fischerova, D.; Guerriero, S.; Moruzzi, M. C.; Colombo, N.; Timmerman, D.; Valentin, L.; Testa, A. C.
ABSTRACT Objectives To describe the sonographic characteristics of borderline ovarian tumor (BOT) recurrence. Methods From the databases of five ultrasound centers, we retrospectively identified 68 patients with histological diagnosis of recurrent BOT who had undergone preoperative ultrasound examination. All recurrences were detected during planned follow‐up ultrasound examinations. Recurrent lesions were described using the terms and definitions of the International Ovarian Tumor Analysis (IOTA) group. Results Sixty‐two patients had a serous BOT recurrence and six a mucinous BOT recurrence. All patients except one were premenopausal, 84% of them being < 40 years old. All but one patient were asymptomatic at diagnosis of the recurrence. Fertility‐sparing surgery of the recurrent tumor was performed in 57/68 (84%) patients. The most frequent ultrasound feature of recurrent serous BOT was a unilocular solid cyst (49/62, 79%) and almost half of the recurrent serous BOTs (29/62, 47%) had multiple papillary projections. In 89% of the recurrent serous BOTs there was at least one papillation with irregular surface and in 73% there was at least one papillation vascularized at color Doppler examination. Recurrent mucinous BOTs appeared mainly as multilocular or multilocular solid cysts (5/6, 83%). Conclusion Sonographic features of recurrent BOT resemble those described by others for different subtypes of primary BOT. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.